2,8-Diheterobicyclo[3.2.1]octane Ring Systems: Natural Occurrence, Synthesis and Properties - Flores, MariFe; Díez, David (Synlett, 2014)
This account describes the developments on the synthesis and reactivity of functionalized 2,8-diheterobicyclo[3.2.1]octanes. The continued interest in the chemistry of these compounds is mainly due to their abundance in Nature, being at the core of numerous families of biologically active natural products, and also as a result of their versatile reactivity, which makes them very useful building blocks with considerable impact in modern organic synthesis. The present article is aimed toward providing a comprehensive coverage of the literature on these heterocyclic scaffolds, including our own contributions, and has been organized according to the nature of the heteroatom embedded in the 2,8-bicyclo[3.2.1]octane framework.1 Introduction2 2,8-Dioxabicyclo[3.2.1]octane Systems2.1 Natural Products2.1.1 Marine Origin: Pectenotoxins, Saliniketals2.1.2 Terrestrial Origin: Fungus (Squalestatins), Plants2.2 Synthetic Products3 2-Aza-8-oxabicyclo[3.2.1]octane Systems3.1 Cyclonucleotides3.2 Diazaimide Derivatives3.3 Systems with a 1,3-Oxazepane Core3.4 2-Aza-8-oxabicyclo[3.2.1]octanes Fused with Aromatic Rings3.5 Other Bicyclic Systems4 2-Thia-8-oxabicyclo[3.2.1]octane Systems4.1 From Sugars4.2 Compounds for Asymmetric Epoxidation4.3 Compounds from Photoreactions of Thioketones5 2-Oxa-8-azabicyclo[3.2.1]octane Systems5.1 Natural Products: Kopsia Alkaloids5.2 Synthetic Products6 2,8-Diazabicyclo[3.2.1]octane Systems6.1 Natural Products: Albomitomicyn6.2 Synthetic Products: Epibatidine Analogues7 2-Thia-8-azabicyclo[3.2.1]octane Systems7.1 Natural Products: Diketopiperazines7.2 Synthetic Products8 Conclusions
Keywords: alkaloids; bicyclic compounds; cycloaddition; natural products; imines